2020
DOI: 10.1037/fam0000604
|View full text |Cite
|
Sign up to set email alerts
|

Are father depression and masculinity associated with father perceptions of maternal gatekeeping?

Abstract: Maternal gatekeeping has been associated with reductions in father involvement and can have a negative impact on the family. Few researchers, however, have focused on how characteristics of the father contribute to gatekeeping. Consequently, this brief report is focused on associations between father depression, father adherence to masculine norms, and father reports of maternal gatekeeping. We further test whether a father's adherence to traditional masculine norms interacts with the relationship between depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…For example, the gatekeeping measure used in the current study has three separate constructs: maternal identity confirmation, standards, and responsibilities (Allen & Hawkins, 1999), whereas the measure by Fagan and Barnett (2003) is focused on maternal control or ownership of parenting. Differences in measures could explain the lack of consistent results between Thomas and Holmes (2019), as well as Schoppe‐Sullivan et al (2015), and the results found in this manuscript. It is also possible that this sample is less likely to adhere to traditional ideas of maternal gatekeeping; the specific sample is newlyweds, many of whom cohabited before marriage.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…For example, the gatekeeping measure used in the current study has three separate constructs: maternal identity confirmation, standards, and responsibilities (Allen & Hawkins, 1999), whereas the measure by Fagan and Barnett (2003) is focused on maternal control or ownership of parenting. Differences in measures could explain the lack of consistent results between Thomas and Holmes (2019), as well as Schoppe‐Sullivan et al (2015), and the results found in this manuscript. It is also possible that this sample is less likely to adhere to traditional ideas of maternal gatekeeping; the specific sample is newlyweds, many of whom cohabited before marriage.…”
Section: Discussionsupporting
confidence: 54%
“…The first hypothesis, that paternal depression would be directly positively associated with maternal gatekeeping, was not supported. We anticipated that this hypothesis would be supported according to the significant results from past research (Thomas & Holmes, 2019). However, other research has also failed to find a significant association between paternal depression and maternal gatekeeping (Schoppe-Sullivan et al, 2015), which shows conflicting results regarding this association.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Similar dynamics have been documented in families experiencing parental incarceration, with children's caregivers functioning as gatekeepers (e.g., [29]). Gatekeeping can be a reflection of power in the coparenting relationship or the gatekeeper's desire to protect the child from a perceived threat or potential harm [66]. The latter may be especially true for caregivers who are worried about their children coming into contact with the criminal justice system because a parent is incarcerated.…”
Section: Discussionmentioning
confidence: 99%